Il '68 e Milano : Triennale di Milano. - Triennale di Milano, 1998; Boeri, Stefano; Calvenzi, Giovanna; De Carlo, Giancarlo; Lucas, Uliano; Rovatti, Pier Aldo (Milano : Leonardo Arte, 1998)
Barattieri, Edoardo ; Basilico, Gabriele ; Battistessa, Walter ; Gardin/Contrasto, Gianni Berengo ; Bonasia, Aldo V. ; Borgese, Giovanna ; Calvenzi, Giovanna ; Campagnano, Marcella ; Cerati, Carla ; Cerchioli, Carlo ; Colombo, Cesare ; Conti, Tonino ; Fracchia, Dino ; Loconsolo, Silvestre ; Lucas, Uliano ; Mattioli, Paola ; Mazzocchi, Gianfranco ; Mulas, Ugo ; Nicolini, Toni ; Perrucci, Massimo ; Radino, Francesco ; Raffaelli, Piero ; Roveri, Alberto ; Schirer, Robi ; Thorimbert, Toni ; Vitali, Massimo ; Zappaterra, Paolo
Il '68 e Milano : Triennale di Milano, 7 maggio - 30 guigno 1998
Italiaans
boek